2019
DOI: 10.1089/tmj.2018.0002
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine-Based Health Coaching Is Effective for Inducing Weight Loss and Improving Metabolic Markers

Abstract: ClinicalTrials.gov identifier NCT03278951.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 35 publications
1
90
1
Order By: Relevance
“…In observational analyses of commercial weight loss participants, a 2017 study reported that videoconference participants were more likely to complete the 11‐week programme but not more likely to lose weight . Most recently, a study team reported from two randomized trials (one of 25 and one of 30 adults with obesity) that those randomized to videoconference arms had significantly greater 12‐week weight loss than those randomized to either in‐person or usual care arms . These two trials provided individual health coaching, and the 2018 trial also provided participants with a wireless watch and weight scale.…”
Section: Introductionmentioning
confidence: 99%
“…In observational analyses of commercial weight loss participants, a 2017 study reported that videoconference participants were more likely to complete the 11‐week programme but not more likely to lose weight . Most recently, a study team reported from two randomized trials (one of 25 and one of 30 adults with obesity) that those randomized to videoconference arms had significantly greater 12‐week weight loss than those randomized to either in‐person or usual care arms . These two trials provided individual health coaching, and the 2018 trial also provided participants with a wireless watch and weight scale.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies focused on individual video counseling for smoking cessation [ 31 , 70 - 72 ], 3 studies focused on alcohol consumption [ 73 - 75 ], 3 studies focused on physical activity [ 76 - 78 ], and 3 studies focused on obesity [ 79 - 81 ]. No trial examined the effectiveness of real-time video counseling on nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…No trial examined the effectiveness of real-time video counseling on nutrition. Most trials were funded by grants from the government [ 76 , 77 , 79 - 81 ] or university [ 71 , 73 ]. One study reported receiving no funding [ 75 ], 1 study was funded by the Craig H. Neilsen Foundation [ 78 ], and 1 study was funded by CureApp Inc [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations